Evaluating the REP-S brief resilience intervention for students in higher education: a multi-study mixed-methods programme of research. Issue 5 (3rd September 2021) - Robinson, Oliver C.; Sebah, Ilham; McNay, Ian; Field, Jennifer; Wragg, Jane; Stevenson, Mandy; Newton, Paul
ABSTRACT: There is currently an unmet need in higher education for a structured, pre-emptive programme of support to help students enhance their resilience to stress. This article presents a mixed-methods evaluation of a transferable biopsychosocial resilience intervention for students – the Resilience Enhancement Programme for Students (REP-S). In Study 1, a randomised control trial showed that participating in the intervention was associated with significantly decreased perceived stress, decreased trait neuroticism and enhanced self-esteem over a period of one month. In Study 2, written and focus-group qualitative data from students provided evidence that the intervention led to perceived positive changes, including sleeping better, dealing more effectively with assessments and managing interpersonal challenges. Future steps in the evaluation of the REP-S are discussed.